Arahan Pengembangan Kawasan Pariwisata Pantai Cacalan Banyuwangi dengan Konsep Community-Based Tourism - Annisa Dwi Cahyani (Fakultas Teknik, 2025)
Based on the Banyuwangi Regency Tourism Development Master Plan, Pantai Cacalan is included in the Natural Tourism Attraction Objects and Cultural Tourism Attraction Objects. In addition, Pantai Cacalan is also included in the Tourism Development Area I (WPP I) Ijen Zone as a Supporting Tourism Attraction Objects. Althought it has a lot of potentials and became a tourist destinations for the locals, the development of Pantai Cacalan has not been carried out properly. The first objective of this study is to determine the priority factors for developing the Pantai Cacalan Tourism Area. In achieving this goal, the Analytical Hierarchy Process (AHP) method is used. The results obtained from AHP are: Environmental Criteria with the sub-criteria of increasing community environmental awareness(0.228); Community Participation criteria with the subcriteria of Benefit Participation(0.516); Social criteria with the sub-criteria of Active Community Organizations(0.447); Economic criteria with the sub-criteria of Increasing Local Community Income(0.638); and Cultural criteria with the subcriteria of Development based from local culture(0.850). The next objective is to develop strategies based on priority factors using SWOT analysis. The results was found that the development of Pantai Cacalan is in quadrant I, where development utilizes the strengths and opportunities of the area.
Entry oleh Arif 2026 Maret 05
Keywords: Development; Local community; Tourism